Accessibility compliance for persons with disabilities for Malaysian green buildings / Chua Fuh Yiing - Chua , Fuh Yiing (2018)
In Malaysia, the introduction of the Green Building Index is a reinforcement of the Green building design agenda although compliance is not made mandatory. At the same time, the Persons with Disabilities Act 2008 Malaysia promotes strongly universal design, where accessibility is the major concern in the built environment. Both the Green Building Index and Persons with Disabilities Act support sustainable development in terms of environmental protection and social equity, respectively. The aim of the research is to investigate the accessibility compliance for the Green buildings in Malaysia through the review of the legislation and regulation. The extent of the accessibility of the building is influenced by the whole development process, including planning, design, post-control and management of the building. The study investigates the accessibility of Green buildings in Malaysia, focusing on whether Persons with Disabilities are able to enter, use and exit public buildings. Research method is conducted via multiple site case study visits to conduct the detached observation with persons with disabilities in Green office building, direct observation through access audit checklist, in which the raw data was collected by the researcher to access the compliance of the accessibility (through the review of reports and policy documents). A comprehensive literature review is conducted to identify the building laws regulating access for persons with disabilities within built environment aspect, especially Green building, in order to achieve accessibility. The difficulties in accessing the built environment by different types of users also being investigated. This multiple site case study is valuable because it identifies the inadequacies of current access provisions for people with disabilities and highlights the areas requiring further improvement. Throughout the study, it shows that the Persons with Disabilities’ needs are not accounted for satisfactorily in Malaysian Green buildings. It is hoped that by conducting this research, the solution can be found to improve the architect’s skill in space planning and to understand the perception of users, through the usage of the Green Building Index, to rate buildings in everyday life.